1997
DOI: 10.1074/jbc.272.12.7810
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Methylation in the Hypermethylated CpG Promoter Region of the Human L1 Retrotransposon

Abstract: We have investigated the function and sequence specificity of DNA methylation in the hypermethylated CpG island promoter region of the endogenous human LINE-1 (L1) retrotransposon family. In nontransformed human embryonic fibroblasts, inhibition of DNA methylation with 5-azadeoxycytidine induced a greater than 4-fold increase in transcription from potentially functional L1 elements without increasing the transcription level of the majority of degenerate elements, implicating hypermethylation in the repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
5
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 46 publications
8
117
5
1
Order By: Relevance
“…In a sequence covering four gene regions, we detected little methylation at these putative CpNpG sites. In another study examining human embryonic fibroblasts, a number of non-CpG methylation sites were identified in the sequence of an L1 retrotransposon (29). The most recent study of importance here was a genome-wide examination of non-CpG methylation in murine embryonic stem cells (26), which showed that methylation occurred at CpA and CpT sites in wildtype embryonic stem cells and different somatic tissues.…”
Section: Discussionmentioning
confidence: 94%
“…In a sequence covering four gene regions, we detected little methylation at these putative CpNpG sites. In another study examining human embryonic fibroblasts, a number of non-CpG methylation sites were identified in the sequence of an L1 retrotransposon (29). The most recent study of importance here was a genome-wide examination of non-CpG methylation in murine embryonic stem cells (26), which showed that methylation occurred at CpA and CpT sites in wildtype embryonic stem cells and different somatic tissues.…”
Section: Discussionmentioning
confidence: 94%
“…For example, chimeric N10 and N12 transcripts were more abundant in JEG 3 rather than NTera2D1 cells, suggesting more efficient transcription from the L1Hs ASP in the former cell line. It should be emphasized that activation and repression of L1Hs transcription and presumably its antisense transcription depend on the methylation status of the genomic L1Hs (37,39). An interesting aspect of L1Hs transcription is that at least in NTera2D1 cells where sense transcription is activated, ASPdirected transcripts complementary to the sense transcripts of about 500 nt are also produced.…”
Section: Discussionmentioning
confidence: 99%
“…We show that this decrease in Alu concentration is accompanied by an increase in long repeats and repeat tracts, the most abundant of which are LINE-1 elements. Long repeats including LINE-1 elements are normally heavily DNA-methylated (Woodcock et al, 1988;Crowther et al, 1991;Woodcock et al, 1997), a feature of heterochromatin. DNA methylation (and heterochromatin in general) has been reported to suppress homologous recombination (Pàldi et al, 1995;Maloisel and Rossignol, 1998;Schnable et al, 1998;Fu et al, 2002;Yao et al, 2002;Yamada et al, 2004;Myers et al, 2005) as well as transposition (Yoder et al, 1997;Walsh et al, 1998;Hirochika et al, 2000;Robertson, 2001;Bird, 2002;Kato et al, 2003).…”
Section: Non-random Repeat Distributions Via Natural Selectionmentioning
confidence: 99%